Housing, Income Inequality and Progressivity of Taxes and Transfers - Peter Siminski; Roger Wilkins (Institute of Labor Economics (IZA), 2025)
We examine the role of owner-occupied housing for income inequality. Departing from related work, we incorporate accrued capital gains, focus on long-run measures of income, and consider implications for tax progressivity. Using Australia as a case study, we show that housing income can have major implications for the apparent level and trends over time of inequality, progressivity of taxes and transfers, as well as the demographic profile of the rich and the poor. When imputed rent and accrued capital gains—neither of which are taxed—are included in the income base, the redistributive impact of income tax is reduced by 40%.
Keywords: D63; R21; H24; 330; inequality; housing; tax progressivity